Impact of land management on soil macrofauna in the Oriental Llanos of Colombia - Decaëns, Thibaud; Lavelle, Patrick M.; Jiménez Jaén, J.J.; Escobar, G.; Rippstein, G (1994)
The effect of different types of land management on the soil macrofauna of the savanna has been assesed using the T.S.B.F. method. Macrofauna of the forest and savanna has a high density (4293 and 2830 ind.m(2)) and moderate biomass (13.6 and 15.3 g.m(-2)). Traditional grazing significantly increase earthworm biomass but does not modify biomass (16.8 g.m(-2)) and density (1971 ind.m(-2)). Burning the savanna leads to a momentarily but important disruption of the soil fauna. After 6 months, soil macrofauna has regained its initial level. When stocking rate increase, contribution to biomass of different groups is modified. These results are probably due to the modification of the soil microclimate and to the imput of cow dung. Improved pastures have an important earthworm population (22.9 to 51.1 g.m(-2)) composed of native species, and a high macrofauna diversity (26 to 32 units). This results from the improving of the quality of the organic matter brought to the soil (litter and cow dung). Annual high input cultivations results in a spectacular decrease, both quantitative and qualitative, in the invertebrate populations (3.2 to 4.3 g.m(-2), 429 to 592 ind. m(-2) and 18 units). This phenomenon may be explained by the effect of the tilling of the soil, the fertilization and by the decrease of the soil organic matter.